Understanding Sleep Challenges and Coping Strategies in Adults with Attention Deficit Hyperactivity Disorder (ADHD) - Nurhayati Nurhayati; Mulya Virgonita I. Winta; MM. Shinta Pratiwi (Psikostudia : Jurnal Psikologi, 2026)
Sleep disturbances are significantly prevalent among adults with Attention Deficit Hyperactivity Disorder (ADHD), yet limited qualitative research has explored the subjective experiences of this population. This qualitative study aimed to investigate the relationship between sleep problems and ADHD in adults, focusing on their lived experiences and adaptive strategies. Using interpretative phenomenological analysis (IPA), semi-structured interviews were conducted with 9 adults diagnosed with ADHD who reported sleep difficulties. Data were analyzed through thematic analysis to identify patterns in participants' experiences. Three main themes emerged: (1) The vicious cycle of sleep disruption and ADHD symptoms, (2) Emotional and cognitive impacts of sleep-ADHD interaction, and (3) Individual coping strategies and adaptation mechanisms. Findings revealed that sleep problems exacerbate ADHD symptoms, creating a complex interplay that affects daily functioning, emotional regulation, and quality of life. Participants developed various adaptive strategies including environmental modifications, routine establishment, and self-medication behaviors. The study provides insights into the subjective experiences of adults with ADHD-related sleep problems and highlights the need for integrated treatment approaches addressing both conditions simultaneously.